THEOREM FOR FIXED POINTS, COMMON FIXED POINTS,COINCIDENCE POINTS BY MODIFIED ITERATIVE SEQUENCE - Abd, Salaw Salman; Nemah, Eman Mohmmed (Al-Nahrain Journal of Science, 2010)
In this paper the technique of convergence for modified Mann and Ishikawa schemes are used to proving many results about the existence of fixed points, common fixed points and coincidence points.